Effectiveness of Antibiotherapy, VAC, and Ostomy in the Treatment of Perianal Abscess: Analysis in a Large Sample of 181 Cases - Güzelyüz, Betül; Taşkın, Halit Eren; Günaydın, Fatma İpek and Hatipoğlu, Engin and Uludağ, Server Sezgin (Cerrahpaşa Medical Journal, 2024)
Objective: To examine the effects of VAC and ostomy in the treatment of perianal abscess and their relationship with the characteristics of the abscess and comorbidities. Methods: Demographic characteristics of patients and characteristics of abscess, VAC, ostomy, hospital stay and complications were examined retrospectively. The Statistical Package for Social Sciences version 26.0 software (IBM Corp.; Armonk, NY, USA) was used. Descriptive methods were used. Data were compared with Fisher Freeman Halton Exact test, Kruskal Wallis and Bonferroni Dunn test. Significance was evaluated at the P < .05 level. Results: Of the total 181 cases, 56.9% (n = 103) were male, their age was 45.33±14.27 years. Uncomplicated recovery in 77.3% (n = 140) of cases; local complications developed in 19.9% (n = 36), systemic complications/mortality in 2.8% (n = 5). Abscesses were perianal+urogenital in 11,6%(n = 21); size was 3.53±2.70 cm. 34,3% (n = 62) had comorbidity, and 11.6% (n = 21) had a fistula. Age, perianal+urogenital location, large abscess, and comorbidities were associated with complications (P= .015, P = .001, P = .048, P = .001,respectively). Fistula-complication relationship wasn’t significant (P = .671). Extended antibiotics were used in 17,1% (n = 31); ostomy in 7.2% (n = 13); 3.3% (n = 6) had VAC. Extended antibiotics and ostomy were associated with complications, but VAC wasn’t (P = .001, P = .001, P = .240, respectively). Secondary healing occurred in 96,7% (n = 175), and primary closure/flap-graft repair in 3.3% (n = 6) of the cases; complication rates were similar (P = .066). The hospital stay was 5.55 ± 9,72 days, and longer in cases with ostomies, VACs, and those with complications (P = .045). Conclusion: The prognosis in perianal abscesses is affected by age, comorbidities, and characteristics of the abscess. Extended antibiotics and ostomy were associated with complications and long hospitalization. Despite obvious local benefits, VAC doesn’t provide sufficient benefit when a negative prognosis is predicted. This shows that some new methods can be given a chance alongside VAC in perianal abscesses, which continues to be a serious problem today. Cite this article as: Güzelyüz B, Taşkın HE, Günaydın Fİ, Hatipoğlu E, Uludağ SS. Effectiveness of antibiotherapy, VAC and ostomy in the treatment of perianal abscess; analysis in a large sample of 181 cases. Cerrahpaşa Med J. 2024;48(3):248-252.